2021
DOI: 10.1186/s13018-021-02574-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of key long non-coding RNAs in resveratrol protect against IL-1β-treated chondrocytes via integrated bioinformatic analysis

Abstract: Background Long non-coding RNAs (lncRNAs) participate in regulation of gene transcription, but little is known about the correlation among resveratrol and lncRNAs. This study aimed to identify and validate the key lncRNAs in resveratrol protect against IL-1β-treated chondrocytes. Methods In this experiment, high-throughput sequencing technique was performed to identify the differentially expressed lncRNAs, miRNAs, and mRNAs between IL-1β-treated ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Additionally, it has been shown that lncRNAs function in regulating KOA apoptosis and are essential targets for the anti-apoptotic activity of RES ( Liu et al, 2018 ; Li et al, 2020 ; Xie et al, 2020 ). Yi et al found that RES can improve apoptosis of KOA chondrocytes by regulating LINC00654, which is believed to be a prospective target for ameliorating KOA ( Yi et al, 2021 ). The above in vitro evidence confirms that RES is considered a promising complementary therapeutic agent for treating KOA by acting on different in vitro chondrocyte models.…”
Section: Preclinical Studies About Res and Its Effects In Koamentioning
confidence: 99%
“…Additionally, it has been shown that lncRNAs function in regulating KOA apoptosis and are essential targets for the anti-apoptotic activity of RES ( Liu et al, 2018 ; Li et al, 2020 ; Xie et al, 2020 ). Yi et al found that RES can improve apoptosis of KOA chondrocytes by regulating LINC00654, which is believed to be a prospective target for ameliorating KOA ( Yi et al, 2021 ). The above in vitro evidence confirms that RES is considered a promising complementary therapeutic agent for treating KOA by acting on different in vitro chondrocyte models.…”
Section: Preclinical Studies About Res and Its Effects In Koamentioning
confidence: 99%
“…High-throughput RNA sequencing of chondrocytes treated with the pro-inflammatory factor IL-1beta, in presence or absence of resveratrol, revealed several differentially expressed lncRNAs, miRNAs, and mRNAs. ( Yi et al, 2021 ). Moreover, combining bioinformatics methods with RT-PCR validation, a competitive endogenous RNA (ceRNA) network, involving the lncRNA LINC00654, miR-210-5p, and the Opioid Growth Factor Receptor Like 1 (OGFRL1), was identified ( Yi et al, 2021 ).…”
Section: Inflammatory Statesmentioning
confidence: 99%
“…( Yi et al, 2021 ). Moreover, combining bioinformatics methods with RT-PCR validation, a competitive endogenous RNA (ceRNA) network, involving the lncRNA LINC00654, miR-210-5p, and the Opioid Growth Factor Receptor Like 1 (OGFRL1), was identified ( Yi et al, 2021 ). In this network, the mutual interaction between lncRNAs and miRNAs may influence cellular metabolic activity and functions as lncRNAs may competitively bind miRNAs, weakening the miRNA responses on the mRNA target and regulating genes at the post-transcriptional level ( Yi et al, 2021 ).…”
Section: Inflammatory Statesmentioning
confidence: 99%
See 2 more Smart Citations